2019
DOI: 10.3389/fimmu.2019.01147
|View full text |Cite
|
Sign up to set email alerts
|

The CD14+HLA-DRlo/neg Monocyte: An Immunosuppressive Phenotype That Restrains Responses to Cancer Immunotherapy

Abstract: Recent successes in cancer immunotherapy have been tempered by sub-optimal clinical responses in the majority of patients. The impaired anti-tumor immune responses observed in these patients are likely a consequence of immune system dysfunction contributed to by a variety of factors that include, but are not limited to, diminished antigen presentation/detection, leukopenia, a coordinated network of immunosuppressive cell surface proteins, cytokines and cellular mediators. Monocytes that have diminished or no H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 135 publications
(139 reference statements)
1
108
0
1
Order By: Relevance
“…Some studies have described MDSCs as HLA-DR -/low CD14 + [7,10,13], whereas some studies have defined MDSCs based on the expression of CD11 and CD33 [12,14]. Recently, HLA-DR -/low CD14 + cells are considered as monocytic MDSCs [15,16]; therefore, we examined the frequencies of HLA-DR -/low CD11b + CD33 + in this study. Second, the selection of study population is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described MDSCs as HLA-DR -/low CD14 + [7,10,13], whereas some studies have defined MDSCs based on the expression of CD11 and CD33 [12,14]. Recently, HLA-DR -/low CD14 + cells are considered as monocytic MDSCs [15,16]; therefore, we examined the frequencies of HLA-DR -/low CD11b + CD33 + in this study. Second, the selection of study population is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Since these markers are also expressed on other immune cells, such as neutrophils (e.g., CD15, CD66b), evaluation of direct immunosuppressive function is mandatory for the definition of MDSCs [28]. The immunosuppressive functions of MDSCs are mediated by several secreted factors, including prostaglandin E2 (PGE2), IL-10, transforming growth factor (TGF)-β, nitric oxide (NO) and arginase 1 (Arg1) for Mo-MDSCs [28,30], and reactive oxygen species (ROS), granulocyte-colony stimulating factor (G-CSF) and Arg1 for G-MDSCs [28]. Since Mo-MDSCs are generated from monocytes, and further differentiate to TAMs, Mo-MDSCs and TAMs in human tumors share several cell surface markers [28,30,31].…”
Section: Significance Of Mdscs In Developing Skin Cancersmentioning
confidence: 99%
“…The immunosuppressive functions of MDSCs are mediated by several secreted factors, including prostaglandin E2 (PGE2), IL-10, transforming growth factor (TGF)-β, nitric oxide (NO) and arginase 1 (Arg1) for Mo-MDSCs [28,30], and reactive oxygen species (ROS), granulocyte-colony stimulating factor (G-CSF) and Arg1 for G-MDSCs [28]. Since Mo-MDSCs are generated from monocytes, and further differentiate to TAMs, Mo-MDSCs and TAMs in human tumors share several cell surface markers [28,30,31]. On the other hand, although several reports have suggested that G-MDSCs are generated from the neutrophil linage, the differentiation of G-MDSCs remains under discussion [28,32].…”
Section: Significance Of Mdscs In Developing Skin Cancersmentioning
confidence: 99%
“…Differences in monocyte HLA-DR levels were confirmed by measuring the median mass intensity on monocytes gated from each individual (Figure 2A, right panel, p=0.057). Classical monocytes (CM) and non-classical monocytes (NCM) differ functionally, being pro-and anti-inflammatory respectively, and also differ in HLA-DR expression 31,32 . Using CD14 and CD16 to delineate each subset -CM (CD14+ CD16-) and NCM (CD14-CD16+) -we found patients' monocytes contained a larger proportion of CM ( Figure 2B and 2C).…”
Section: Classical Monocytes Are Enriched In Pediatric Cancer Patientsmentioning
confidence: 99%